Structural Transformation and Labor Market Performance in Ghana - Nxumalo, Mpumelelo; Raju, Dhushyanth (World Bank, Washington, DC, 2020)
Structural transformation can spur economic growth and development if it increases overall productivity growth. A labor market environment that enables workers and enterprises to transition smoothly across sectors and into more productive economic pursuits can enhance the effect of structural transformation on economic growth. This study examines Ghana’s recent record of structural transformation and labor market performance. Based on the findings, the study proposes ways to further transform the country’s economy, in a way that stimulates stronger, sustained growth and produces gainful, productive, and inclusive private employment. The COVID-19 (coronavirus) pandemic and associated global economic crisis have posed a substantial setback to Ghana’s economic progress and plans, but these challenges also underscore the need for structural transformation that can both strengthen economic performance and improve labor conditions and outcomes.